2016
DOI: 10.1111/jpn.12485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical form of starter and forage provision to young calves on blood metabolites, liver composition and intestinal morphology

Abstract: This study evaluated the effects of physical form of starter feed and forage provision on the performance, blood metabolites, liver composition and intestinal morphology of dairy calves. Individually housed calves (n = 52; body weight = 41.5 ± 2.5 kg) were randomly allocated (n = 13 per treatment) to one of the following four treatments: (i) ground starter feed (GS; mean particle size = 0.72 mm in diameter), (ii) textured starter feed (TS; mean particle size = 3.61 mm in diameter, including steam-flaked corn a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…In the current study, no differences were observed in plasma concentrations of triglycerides in preweaning calves. The lack of starter physical forms effects on plasma concentration of glucose and triglycerides in our study was consistent with the results of Moeini et al (2017), who found similar plasma glucose and triglycerides in calves fed ground starters (with a mean particle size of 0.72 mm in diameter) than those fed TF starters (with a mean particle size of 3.61 mm in diameter plus steam-flaked corn and barley). Glucose and BHB data for the effect of forage provision (15% of DM) to calves in the current study was consistent with the results of Mirzaei et al (2017), who observed similar plasma glucose levels between calves supplemented and not supplemented with forage, but in contrast to some previous studies (Khan et al, 2011;Terré et al, 2013) in which inclusion of forage in the starter diets increased plasma BHB concentrations in dairy calves.…”
Section: Blood Metabolites and Rumen Phsupporting
confidence: 92%
“…In the current study, no differences were observed in plasma concentrations of triglycerides in preweaning calves. The lack of starter physical forms effects on plasma concentration of glucose and triglycerides in our study was consistent with the results of Moeini et al (2017), who found similar plasma glucose and triglycerides in calves fed ground starters (with a mean particle size of 0.72 mm in diameter) than those fed TF starters (with a mean particle size of 3.61 mm in diameter plus steam-flaked corn and barley). Glucose and BHB data for the effect of forage provision (15% of DM) to calves in the current study was consistent with the results of Mirzaei et al (2017), who observed similar plasma glucose levels between calves supplemented and not supplemented with forage, but in contrast to some previous studies (Khan et al, 2011;Terré et al, 2013) in which inclusion of forage in the starter diets increased plasma BHB concentrations in dairy calves.…”
Section: Blood Metabolites and Rumen Phsupporting
confidence: 92%
“…Whole grains in textured feeds may be more effective in supporting rumen health and animal performance compared with highly processed grains (Terré et al, 2015). Moeini et al (2017) fed calves diets containing 23% corn and 25% barley with soybean meal (34%) and other ingredients in ground, pelleted, or textured (steam flaked) forms. A fourth treatment included ground diet plus 10% chopped alfalfa hay.…”
Section: Effect Of Cs Form On Total-tract Digestibilitymentioning
confidence: 99%
“…Increasing the level of forage that is blended with starter reduced the growth of calves (Hill et al, 2010(Hill et al, , 2012, and approximately 1.5% NDF from forage has optimized growth from 8 to 16 wk of age (Hill et al, 2010). Others (Moeini et al, 2017;Pazoki et al, 2017) have reported that addition of 10% forage to ground starter increased DMI and BW gain to 70 d of age and improved intestinal morphology compared with pelleted or ground starters without forage. A meta-analysis (Imani et al, 2017) found that ADG was greater when calves were fed >10% forage compared with <10% forage.…”
Section: Introductionmentioning
confidence: 99%